Genistein transfersome-embedded topical delivery system for skin melanoma treatment: in vitro and ex vivo evaluations - Amira Motawea; Sara N. Maria; Doaa N. Maria; Monica M. Jablonski; Mohamed Moustafa Ibrahim (Taylor & Francis Group, 2024)
Skin melanoma is considered the most dangerous form of skin cancer due to its association with high risk of metastasis, high mortality rate and high resistance to different treatment options. Genistein is a natural isoflavonoid with known chemotherapeutic activity. Unfortunately, it has low bioavailability due to its poor aqueous solubility and excessive metabolism. In the current study, genistein was incorporated into transferosomal hydrogel to improve its bioavailability. The prepared transferosomal formulations were characterized regarding: particle size; polydispersity index; zeta potential; encapsulation efficiency; TEM; FTIR; DSC; XRD; in vitro drug release; viscosity; pH; ex vivo anti-tumor activity on 3D skin melanoma spheroids and 1-year stability study at different storage temperatures. The optimized formulation has high encapsulation efficiency with an excellent particle size that will facilitate its penetration through the skin. The transfersomes have a spherical shape with sustained drug release profile. The anti-tumor activity evaluation of genistein transfersome revealed that genistein is a potent chemotherapeutic agent with enhanced penetration ability through the melanoma spheroids when incorporated into transfersomes. Stability study results demonstrate the high physical and chemical stability of our formulations. All these outcomes provide evidence that our genistein transferosomal hydrogel is a promising treatment option for skin melanoma.